Lifespan and Associated Factors of Peripheral Intravenous Cannula Among Hospitalized Children in Public Hospitals of the Gurage Zone, Ethiopia, 2021 - Mewahegn AA; Tadesse B; GebreEyesus FA; Tarekegn TT; Amlak BT; Emeria MS; Temere BC; Terefe TF; Zewudie BT; Geletie HA; Mengist ST (Dove Medical Press, 2022)
Agerie Aynalem Mewahegn, Betelhem Tadesse, Fisha Alebel GebreEyesus, Tadesse Tsehay Tarekegn, Baye Tsegaye Amlak, Mamo Solomon Emeria, Bogale Chekole Temere, Tamene Fetene Terefe, Bitew Tefera Zewudie, Haymanot Abebe Geletie, Shegaw Tesfe Mengist Department of Nursing, College of Medicine and Health Sciences, Wolkite University, Wolkite, EthiopiaCorrespondence: Agerie Aynalem Mewahegn, Department of Nursing Ethiopia, College of Medicine and Health Sciences, Wolkite University, PO Box 07, Wolkite, Ethiopia, Tel +251 915715727, Email aynalemagerie21@gmail.comBackground: Peripheral intravenous cannulas are routinely used in hospital-admitted children requiring intravenous therapy. The majority of peripheral IVC lines are removed before completion of therapy due to cannula complications in children. Peripheral intravenous cannula securing is a painful procedure for children, so recognizing the variables associated with the peripheral intravenous cannula lifespan would help decrease the complications and increase the duration of cannula patency.Objective: The main aim of this study was to determine the lifespan and associated factors of peripheral intravenous cannula among hospitalized children in Gurage zone public hospitals, Ethiopia, 2021.Methods: We conducted an institution-based cross-sectional study design among 422 admitted children in public hospitals of the Gurage zone using a systematic random sampling technique. We collected data from interviews of parents using structured questionnaires and direct observations using checklists. The data was coded and entered into EPI-DATA version 3.1 and exported to SPSS version 25 for analysis. Bivariable and multivariable analysis was used by using a binary logistic regression model. Finally, the variables with a p-value of < 0.05 with a 95% confidence interval (CI) from the multivariable analysis were considered statistically significant.Results: One hundred and sixty-six children (41.4%) had a short cannula lifespan (below 30 h). Multivariable logistic regression analysis showed that neonatal intensive care unit (NICU) [AOR = 4.975; 95% CI (2.811- 8.805)], reason for removal (complication) [AOR = 3.277; 95% CI (1.924- 5.583)], fluid [AOR = 2.285; 95% CI (1.274- 4.100)], and blood transfusion [AOR = 2.407; 95% CI (1.005- 5.572)] were the statistically significant variables associated with the lifespan of a peripheral intravenous cannula.Conclusion and Recommendation: The proportion of the short lifespan of the peripheral intravenous cannula was higher in hospitalized children and health care providers better to use low concentration electrolytes, low osmotic pressure, and weak alkalinity fluid. The cannula access might be the responsibility of the health-trained staff, and conserving immediate removal upon the presence of a signal that indicates a complication.Keywords: lifespan, peripheral intravenous cannula, associated factors, hospitalized children